Integrasi Kawasan Wisata Terpadu Kota Padang: - Putra, Hari Setia; Editiawarman, Editiawarman; Saputra, Dika; Vidriza, Ullya (JURNAL DESTINASI PARIWISATA; Vol 9 No 2 (2021): VOL 9, NO 2 (2021): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2021.v09.i02.p08, 2021)
This study aims to analyze the integration of tourist attractions in tourism object integrations of Pantai Air Manis, Gunung Padang, and Pantai Padang on the business side. This research used descriptive and inductive and inductive analysis with multiple regression methods and purposive sampling techniques to collect the data. Furthermore, to know the influence of tourism expenses, government assistance, economic activity, and the investment to tourism objects integration in Padang City. This study found the integration of tourism objects in Padang are working relatively well with the average integration degrees at 70,68 percent based on integration rage 59,60-82,00 percent. Tourism expenses, investment, and government assistance have a significant effect on tourism integration. This study recommends West Sumatra government increase the supports and investment to attract more tourists at tourism object integration in Padang City. Keywords: Tourism Objects Integration, Tourism Expenses, Transportation Investment